2015
DOI: 10.1055/s-0034-1399293
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Evaluation of Carotid Atherosclerosis in Post-Radiotherapy Nasopharyngeal Carcinoma Patients, Type 2 Diabetics, and Healthy Controls

Abstract: To comprehensively evaluate and compare the degree of carotid atherosclerosis in patients treated with radiotherapy (RT) for nasopharyngeal carcinoma (NPC) and in patients with type 2 diabetes mellitus (DM), and using healthy subjects as controls. The present study recruited 69 post-RT NPC patients without conventional cardiovascular risk factors, 70 type 2 diabetic patients without previous RT, and 76 healthy controls without conventional cardiovascular risk factors and previous RT. For each participant, 5 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 35 publications
1
16
1
Order By: Relevance
“…The patients were asked to lie on the examination couch with their heads slightly reclined and turned away from the side that was assessed. 20,27 CIMT was measured manually in triplicates in three different angles (anterior, lateral, posterior) at the far wall of the left and right common carotid artery (CCA) 1 cm proximal of the carotid bulb. The measurements were made in plaque-free sequences of the CCA.…”
Section: Data Collectionmentioning
confidence: 99%
“…The patients were asked to lie on the examination couch with their heads slightly reclined and turned away from the side that was assessed. 20,27 CIMT was measured manually in triplicates in three different angles (anterior, lateral, posterior) at the far wall of the left and right common carotid artery (CCA) 1 cm proximal of the carotid bulb. The measurements were made in plaque-free sequences of the CCA.…”
Section: Data Collectionmentioning
confidence: 99%
“…Our group previously reported that no significantly difference in CIMT existed in radiation-induced carotid atherosclerosis (post-RT NPC patients) compared to non-radiation-induced CA (diabetes patients without RT) (p cor =0.732), and higher CIMT was associated to male gender (p cor <0.01) and advanced age (p cor <0.01) (12). In present study, radiation-induced atherosclerosis was with a higher CIMT and more plaque numbers.…”
Section: Discussionmentioning
confidence: 83%
“…Rupture and erosion of CP may cause emboli, and induce the cerebrovascular events. Therefore, CA with the presence of CP increase the risk of cerebrovascular diseases (8,(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to conventional two-dimensional RT (2D-RT), IMRT has been reported to have decreased risk of temporal lobe injury 9 and mastoiditis 10 . Nonetheless, the influence of IMRT on carotid stenosis remains unknown, nor is there a routine to screen patients post RT for carotid stenosis during follow up 11 . Therefore, to investigate the incidence of carotid artery stenosis (≥50%) and the risk factors with IMRT, we retrospectively analyzed 233 cases of NPC treated with IMRT, and compared with those treated with 2D-RT using Doppler ultrasound.…”
Section: Introductionmentioning
confidence: 99%